Institutional distances and equity-based entry modes: A systematic literature review - Moreira da Silva, F.; Ogasavara, M. H.; Pereira, R. (Management Review Quarterly, 2024)
The institutional distance between home and host countries influences the benefits and costs of entry into markets where a firm intends to conduct business. Entry mode choice is a function of a firm's strategy to increase its competitiveness, efficiency, and control over resources that are critical to its operations. This systematic literature review aims to explain the influence of institutional distances on equity-based entry modes in international markets. The present study contributes to the literature on international business using institutional theory to address the entry mode, and by analyzing the nature of the constructs used to measure the influence institutional distances have on the choice of entry mode into foreign markets.